2016
DOI: 10.3892/mmr.2016.4859
|View full text |Cite
|
Sign up to set email alerts
|

Association of the hERG mutation with long-QT syndrome type 2, syncope and epilepsy

Abstract: Mutations in the human ether-à-go-go-related gene (hERG) are responsible for long-QT syndrome (LQTS) type 2 (LQT2). In the present study, a heterozygous missense mutation (A561V) linked to LQT2, syncope and epilepsy was identified in the S5/pore region of the hERG protein. The mutation, A561V, was prepared and subcloned into hERG-pcDNA3.0. Mutant plasmids were co-transfected into HEK-293 cells, which stably express wild-type (WT) hERG, in order to mimic a heterozygous genotype, and the whole-cell current was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Whole‐cell currents were recorded in cells expressing homozygote WT‐hERG and heterozygous F463L‐hERG with and without dofetilide (1 µM) as previously described (Li et al, ). As the protocol shown in the inset, the holding potential was maintained at −90 mV, and tail currents were recorded at a level of −40 mV for 4 s after depolarizing pulses from −60 mV to +60 mV in 10 mV increments for 2 s. Representative traces were from cells expressing WT‐hERG and heterozygous F463L with and without dofetilide, respectively (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Whole‐cell currents were recorded in cells expressing homozygote WT‐hERG and heterozygous F463L‐hERG with and without dofetilide (1 µM) as previously described (Li et al, ). As the protocol shown in the inset, the holding potential was maintained at −90 mV, and tail currents were recorded at a level of −40 mV for 4 s after depolarizing pulses from −60 mV to +60 mV in 10 mV increments for 2 s. Representative traces were from cells expressing WT‐hERG and heterozygous F463L with and without dofetilide, respectively (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…The hERG channel currents were elicited by previously described voltage‐clamp protocol that is a standard protocol used to study I Kr in our laboratory (Figure 1A). 3 Briefly, the holding potential was maintained at −80 mV, and the tail currents were elicited at a level of 40 mV for 4 seconds after depolarizing pulses from −60 mV to +60 mV in 10‐mV increments for 4 seconds.…”
Section: Resultsmentioning
confidence: 99%
“…Whole‐cell patch clamp was applied to record the hERG currents as previously described 3 . Briefly, cells were incubated with 30 µmol/L posaconazole or vehicle for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Long QT syndrome (LQTs) is an inherited cardiac arrhythmia syndrome that is associated with syncope and sudden death (1-3). It has been shown that mutations exist in 15 genes encoding either ion channels or structural proteins associated with LQTs (4-7).…”
Section: Introductionmentioning
confidence: 99%